Perancangan User Experience pada Aplikasi Bahasa Daerah Kalimantan Barat dengan Pendekatan Human Centered Design (HCD) (Studi Kasus: Balai Bahasa Kalimantan Barat) - Salsabila Ikramul Maram; Herman Tolle; Lutfi Fanani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2023)
Nowadays, West Kalimantan local languages are hardly accessible which makes these languages difficult to blend and unfamiliar to the general public. Balai Bahasa Kalimantan Barat, a government body whose mission is to introduce and conserve West Kalimantan local languages, faces some challenges in introducing the local languages to the general public since their online accessibility is still inadequate, not to mention in the form of an application. Therefore, an application is designed to help Balai Bahasa Kalimantan Barat to introduce and conserve West Kalimantan local languages. The application uses Human Centered Design (HCD) which aims to build a system that fulfills the users' needs and is informative, attractive, highly efficient and effective. The application is tested with Usability Testing and UEQ. The Usability Testing resulted in an effectivity of 97% and a time-based efficiency of 0,120 goals/s. Meanwhile, the user satisfaction result is 77% which qualifies as B class and is categorized as good. The user experience test with UEQ shows the benchmark result for the user: Attractiveness 2.35 (Excellent), Perspicuity 1.98 (Good), Efficiency 2.28 (Excellent), Dependability 2.08 (Excellent), Stimulation 2.18 (Excellent), dan Novelty 1.58 (Good).